Community economic development and the rise of ethno‐cultural entrepreneurialism in francophone Manitoba. (2nd March 2015) - Picton, Roger M.; Skinner, Mark W.
<x xml:space="preserve">Abstract</x> This article examines the evolving concept and practice of "cultural entrepreneurialism." Drawing on interviews with community‐based organizations in francophone Manitoba, it extends research on "social entrepreneurialism" by investigating the increasing role played by ethno‐cultural organizations in community economic development. A thematic analysis reveals how community economic development has been adapted to historically—and geographically—grounded cultural and institutional legacies. The findings show how Franco‐Manitoban community organizations formulated a particular mix of social entrepreneurialism infused with cultural practice and upheld an expansive view of community economic development. Scholars need to consider how everyday cultural practices and ethno‐cultural territory influence how community‐based organizations engage in local economic development. Le développement économique communautaire et l'essor de l'entrepreneuriat ethnoculturel au Manitoba français Cet article s'intéresse au concept et à la pratique en évolution de « l'entrepreneuriat culturel ». Se fondant sur des entrevues menées auprès d'organismes communautaires du Manitoba français, l'article s'inscrit dans le prolongement des travaux de recherche en cours sur « l'entrepreneuriat social » en explorant le rôle grandissant joué par les organisations ethnoculturelles dans le développement économique communautaire. Une analyse par thème laisse entrevoir comment le développement économique communautaire a fait l'objet d'aménagements établis sur les bases historiques et géographiques du patrimoine culturel et institutionnel. Il en ressort que les organisations communautaires francophones du Manitoba ont pu mettre au point leur propre vision qui conjugue l'entrepreneuriat social à la pratique culturelle et ainsi défendre une perspective plus étendue du développement économique communautaire. Une des questions que les chercheurs doivent se poser est celle de l'influence que peuvent exercer les pratiques culturelles quotidiennes et le territoire ethnoculturel sur la manière dont les organisations communautaires se lancent dans le développement économique local.